POTENSI PATCH MUKOADHESIF KOMBINASI EKSTRAK ETANOL DAUN SIRIH HIJAU (PIPER BETLE L.), GAMBIR (UNCARIA GAMBIR), DAN BIJI PINANG (ARECA CATECHU) PADA PENYAKIT PERIODONTAL - Mahera Perdana Kusuma; Nilasary Rochmanita Suparno (Muhammadiyah University Press, 2021)
Periodontal disease is an inflammatory disease that affects the supporting tissues of the teeth and is caused by the accumulation of bacteria in the subgingival area. Giving drugs such as antibiotics and anti-inflammatory cause resistance because people can consume them freely, so that natural ingredients from a combination of green betel leaf, gambier, and areca nut can be the right alternative because they have synergistic antibacterial compound. The purpose og this literature review is to determine the potential of mucoadhesive patches combined with ethanol extract of green betel leaf, gambier, and areca nut on the case that cause periodontal disease. Green betel leaf, gambier, and areca nut are often used as medicinal ingredients because they contain many antibacterial compounds that are bacteriostatic, making it possible to combine these three natural ingredients in the preparation of mucoadhesive patches to reduce the bacterial population in periodontal disease. The conclusion from this literature review is that the mucoadhesive patch combined with ethanol extract of green betel leaf, gambier, and areca nut has the potential to reduce colonization of bacteria that cause periodontal disease by inhibiting the growth of periodontal bacteria.